Consumer knowledge about dietary fibre – Results of a national questionnaire survey - Szucs, Viktoria (2016)
Introduction: Dietary fibres are key elements of healthy and balanced diet. Aim: The aim of the present study was to explore consumers’ knowledge considering fibre, their role in the purchasing decisions, and the cognition of the currently used as well as the possible information sources to encourage the fibre consumption. Method: A questionnaire survey was conducted with 303 respondents. Results: Knowledge about the fibre sources has showed a kind of uncertainty of the respondents, while knowledge about their possible health effects was relatively profound. Internet appeared as a remarkable information source in the topic; however, results pointed out the importance of education, too. Participants more often consuming foodstuffs rich in fibre, women and respondents over 45 years old showed conscious attitudes regarding fibres. Conclusions: Guidelines and education containing authentic information and practical elements are essential, and as a result, consumers’ latent knowledge will appear in their conscious food choice decisions.